HiCRes: a computational method to estimate and predict the genomic resolution of Hi-C libraries. Issue 6 (20th December 2021) - Marchal, Claire; Singh, Nivedita; Corso-Díaz, Ximena; Swaroop, Anand
Abstract: Three-dimensional (3D) conformation of the chromatin is crucial to stringently regulate gene expression patterns and DNA replication in a cell-type specific manner. Hi-C is a key technique for measuring 3D chromatin interactions genome wide. Estimating and predicting the resolution of a library is an essential step in any Hi-C experimental design. Here, we present the mathematical concepts to estimate the resolution of a dataset and predict whether deeper sequencing would enhance the resolution. We have developed HiCRes, a docker pipeline, by applying these concepts to several Hi-C libraries.